The Application of Digital Media on Building Luxury Brand Awareness - Phan, Thi Thuy Trang; Zlatić, Marija; Neumannová, Pavla; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This thesis is conducted on the purpose of exploring the current implementation of digital media to build luxury brand awareness. It applies available knowledge of luxury marketing from leading scholars, most up-to-date data findings and reports from world-class research agencies. The problem space was identified from the changing path-to-purchase of new luxury customers forces that reveals how digital media has been influencing customer’s decision on choosing luxury brands. The study adopts a pragmatic approach that appears best suited to the research problem. Based on available literature, recent data, real-life cases and an organic online survey, the research was able to visualize the core application of selected digital media tools that are essential to attain more brand awareness. This includes social media marketing, e-commerce strategy that links to luxury omnichannel and disruptive technologies which will reshape the industry in a near future.Nowadays, approximately 80% of luxury purchases are proved to be digitally influenced (McKinsey, 2018). New luxury customers are said to be trend followers and often buy from top-of-mind brands. Market-winning luxury brands are those that realize how their customers engage on the Internet. They must successfully immerse digital marketing to existing branding strategies but persist in being exclusive. The approach is to build a digital ecosystem that intertwines various digital media tools to strengthen luxury brands advocacy. Such ecosystem will be introduced towards the end of the thesis and modified by findings from the survey to come up with diligent recommendations.
Vedoucí práce: Marija Zlatić
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses